Remote teaching of courses other than Polish in the study of the School of Polish for Foreign Students of the University of Lodz - Góralczyk-Mowczan, Paula; Maćkowiak, Rafał (Activation-innovation-inspiration in (glotto) didactics, 2022)
The article is a continuation of research on the evaluation by students of remotely conducted classes at the Polish Language Center for Foreigners of the University of Lodz during the COVID-19 pandemic. The text presents the results of the survey (conducted after the first semester of distance learning in the 2020/2021 academic year) regarding the assessment of subjects other than Polish, i.e. mathematics, biology, physics, chemistry, history, geography and knowledge about Poland. The research found out what, according to the students, should be improved in online learning, and what satisfied them. Thanks to this, we learned about the potential directions of development that may strengthen the teaching potential of an individual.